Renal replacement therapy in patients with familial Mediterranean fever - Bahman Bashardoust; Bahram Bashardoust; Maryam Ghavami; Nasrin Shami (Society of Diabetic Nephropathy Prevention, 2022)
One of the causes of end-stage renal disease (ESRD) in some countries is the renal involvement caused by the complications of the familial Mediterranean fever (FMF). Amyloidosis is of the most important complications of FMF that can lead to ESRD. We report our experiences of FMF patients with ESRD who received hemodialysis and kidney transplantation over the past 17 years. Of nine patients, four had amyloidosis, two had focal segmental glomerulosclerosis (FSGS), one had IgA nephropathy, and two did not undergo biopsy because their kidneys were atrophic. Of the nine patients, one died of amyloidosis. Seven patients had kidney transplantation and one patient is currently undergoing dialysis. Six patients were transplanted from a living donor and one from a cadaver. The ultrasound examination revealed that five patients had bilateral kidney atrophy, four patients had normal size kidney with amyloidosis. None of the seven patients who underwent renal transplantation had a history of rejection. Kidney transplantation and hemodialysis in patients with FMF is similar to those with other ESRD etiologies.